THE EFFECT OF REPLACING COMMERCIAL DIETS WITH MAGGOT FLOUR (Hermetia illucens) ON THE PERFORMANCE OF LAYING CHICKENS - K. W., Prassetia; Astawa, I P. A.; Wirapartha, M. (Jurnal Peternakan Tropika, 2024)
This study aims to determine the effect of replacing commercial rations with maggot flour (Hermetia illucens) on the performance of laying hens which has been carried out in Busungbiu Village, Busungbiu District, Buleleng Regency, Bali for 4 weeks. This study used 444 a completely randomized design (CRD) consisting of 4 treatments and 4 replications. Each replication consisted of ten laying hens. The ration treatment is P0 (commercial ration without maggot meal); P1 (commercial diet with 5% maggot meal); P2 (commercial diet with 10% maggot meal); P3 (commercial ration with 15% maggot meal). The variables observed were feed consumption, hen day production, egg weight and also feed conversion. The results of this study showed that replacing commercial rations with maggot flour (Hermetia illucens) P1, P2, P3 significantly (P<0.05) increased egg weight compared to P0 but the ration consumption, hen day production and ration conversion were not significantly different (P>0.05). Based on the results of this research, it can be concluded that replacing commercial rations with 5%, 10% and 15% maggot flour increases egg weight and has no effect on ration consumption, hen-day production and ration conversion.